2019
DOI: 10.1007/s10295-019-02207-0
|View full text |Cite
|
Sign up to set email alerts
|

Mild hydrothermal pretreatment of sugarcane bagasse enhances the production of holocellulases by Aspergillus niger

Abstract: Holocellulase production by Aspergillus niger using raw sugarcane bagasse (rSCB) as the enzyme-inducing substrate is hampered by the intrinsic recalcitrance of this material. Here we report that mild hydrothermal pretreatment of rSCB increases holocellulase secretion by A. niger. Quantitative proteomic analysis revealed that pretreated solids (PS) induced a pronounced up-regulation of endoglucanases and cellobiohydrolases compared to rSCB, which resulted in a 10.1-fold increase in glucose release during SCB sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…2 C). The proteins without signal peptides in the secretome may be extracellular proteins secreted by alternative secretion pathways or intracellular proteins leaked as earlier reported [ 9 , 18 ].
Fig.
…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…2 C). The proteins without signal peptides in the secretome may be extracellular proteins secreted by alternative secretion pathways or intracellular proteins leaked as earlier reported [ 9 , 18 ].
Fig.
…”
Section: Resultsmentioning
confidence: 91%
“…The higher number of xylan-degrading enzymes detected across the different secretomes was similar to that reported for Aspergillus niger cultivated on pretreated SCB. This diversity in xylanases has been attributed to the complexity of the acetylated glucuronoarabinoxylan present in SCB [ 9 , 19 ]. Furthermore, amidst the CAZymes detected were pectin-degrading enzymes that included rhamnogalacturonase (GH28) and rhamnogalacturonan acetylesterase (CE12), both responsible for degradation of rhamnogalacturonan I, the main pectic component in sugarcane cell walls [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bioconversion process of this biomass requires several arrays of lignocellulolytic enzymes which act synergistically to deconstruct the tightly packed polymeric carbohydrate components into monomeric sugars that can subsequently be converted to fuels and valuable chemicals. Previous studies have shown that several biomass conversion processes rely on biomass pretreatment before enzymatic hydrolysis, to remove lignin and reduce the recalcitrance nature of the biopolymer 10 12 . However, this process often leads to a reduction in the hemicellulose content 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The bioconversion process of this biomass requires several arrays of lignocellulolytic enzymes which acts synergistically to deconstruct the tightly packed polymeric carbohydrate components into monomeric sugars that can subsequently be converted to fuels and valuable chemicals. Previous studies have shown that several biomass conversion processes rely on biomass pretreatment before enzymatic hydrolysis, to remove lignin and to reduce recalcitrance nature of the biopolymer [9][10][11] . However, this process often leads to reduction in the hemicellulose content 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this process often leads to reduction in the hemicellulose content 12 . Owing to this challenge, several mild pretreatment techniques are getting developed so as to reduce the loss in hemicellulose content of lignocellulosic biomass thereby giving attention to more characterization of hemicellulases and notable accessory enzymes bene cial to biomass deconstruction 9 . Hemicellulases such as xylanases, lichenases and laminarases which are endoglucanases active on mixed-glucans have earlier been reported to improve the hydrolysis of xylan and cellulose thereby contributing to the reduction of enzyme dosage for complete biomass sacchari cation 12,13 .…”
Section: Introductionmentioning
confidence: 99%